Differences in Biology Students’ Self-Regulation During Online and Offline Learning and Its Relationship to Learning Outcomes - Jk, Adi Kus Rochman; Listyorini, Dwi; Rohman, Fatchur; Affriyenni, Yessi (Jurnal Pendidikan Sains, 2024)
The cultivation of self-regulatory skills holds paramount importance for individuals’ future success, particularly in the context of evolving educational modalities prompted by the Covid-19 pandemic. As learning transitions between online during the pandemic and offline post-pandemic, understanding the nuances of self-regulation becomes imperative. Thus, this study sought to achieve three objectives: (1) analyzing disparities in student self-regulation between online and offline settings, (2) examining the interplay between online and offline self-regulation, and (3) scrutinizing the relationship between self-regulation and learning outcomes. Employing a methodological approach involving questionnaire administration and interviews, data analysis was conducted utilizing the Wilcoxon Signed Ranks test and Spearman’s rho test. The findings reveal that offline self-regulation markedly surpasses its online counterpart, indicating a significant discrepancy. Furthermore, a robust correlation is observed between students’ self-regulation during online learning and the subsequent development of offline self-regulation. Additionally, while the correlation between self-regulation and learning outcomes is characterized as weak, it underscores the tangible influence of self-regulation on enhancing academic achievements. These findings underscore the critical role of self-regulation in navigating diverse learning environments and underscore the need for targeted interventions to bolster students’ self-regulatory competencies.DOI: 10.17977/jps.v12i12024p007